Facilitating knowledge of mental health nurses to undertake physical health interventions: a pre‐test/post‐test evaluation. (7th March 2014) - Hemingway, Steve; Clifton, Andrew; Stephenson, John; Edward, Karen‐Leigh
<x xml:space="preserve">Abstract</x> Aim The aim of this project was to develop and deliver an evidence‐based educational package with a physical and mental health focus to clinicians and other health care workers in mental health settings. Background For individuals who experience mental disorders, pharmacotherapy is often considered as a first line of treatment. However, owing to adverse drug reactions and pre‐existing physical conditions, outcomes for clients/service users may be compromised. Mortality and morbidity rates of people diagnosed with a serious mental illness caused by physical health conditions do not compare favourably with the general population. This paper reports on a physical skills project that was developed in collaboration between the University of Huddersfield and South West Yorkshire Partnership Foundation Trust. Method Pre–post study design: five workshops were conducted in the fields of intramuscular injections, diabetes, health improvement, oral health and wound care. A total of 180 pairs of questionnaires to assess practitioner and student skills and knowledge were administered to participants before and after workshops. All workshops resulted in a statistically significant improvement in subject skills and knowledge scores (P < 0.001 in all cases). Questionnaires also elicited participant satisfaction with the workshops: over 99% of participants reported being 'satisfied' or 'very satisfied' with the workshops. Implications for nursing management Mental health nurses are the largest group of registered practitioners working in the mental health setting and thus need to be harnessed to make a positive contribution to the improvement of the physical health status of service users with a serious mental illness.